2011
DOI: 10.1590/s0103-51502011000300009
|View full text |Cite
|
Sign up to set email alerts
|

Perfil sociodemográfico e profissional de fisioterapeutas e origem das suas concepções sobre ética

Abstract: INTRODUÇÃO: Os estudos sobre o perfil de profissionais de saúde são informações relevantes para possibilitar aos órgãos de saúde, às instituições de ensino e aos órgãos de classe o planejamento de ações assistenciais e educativas. As ações em saúde e suas avaliações precisam levar em consideração o perfil dos profissionais disponíveis e o contexto macroeconômico de determinados grupos, de acordo com a época e a região em que se encontram, para o sucesso e a qualidade das atividades planejadas. OBJETIVO: Conhec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
19

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 6 publications
(6 reference statements)
2
3
0
19
Order By: Relevance
“…These data are similar to the age and gender group cited in the literature as the profile of this professional category (10,11).…”
Section: Resultssupporting
confidence: 86%
“…These data are similar to the age and gender group cited in the literature as the profile of this professional category (10,11).…”
Section: Resultssupporting
confidence: 86%
“…This study showed the prevalence of female physical therapists in São Paulo (80%) (which is consistent with other studies 7,11,13,14,[17][18][19][20][21] ) and graduated after the year of 2001 in private institutions 19,22 . As the undergraduate program in physiotherapy lasts between 4 and 5 years, we expected the growth in the number of professional graduated after the year of 2001, reflecting the Higher Education Expansion plan adopted in 1997.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible to notice the interest of physical therapist at the field of public health. However, there is still needed to increase positions in the public health system and a more inclusive policy in order to cover professionals in services (11).…”
Section: Discussionmentioning
confidence: 99%